Description of the Aegean and other islands a facsimile of the manuscript at the James Ford Bell Library, University of Minnesota - Christophorus de Bondelmontibus 1385-1431; Martellus Germanus, Henricus (Italica Press historical travel series, 2018)
"A facsimile, transcription and translation of the James Ford Bell Library (University of Minnesota) manuscript of Cristoforo Buondelmonti's "Descriptio Arcipelagi Et Cicladum Aliarumque Insularum" copied by Henricus Martellus Germanus"...